Report on teacher training in Trinidad and Tobago - Greig, James W. (Institute of Education, UWI)
This report discusses the following issues, which are deemed critical, with respect to the preparation of teachers in Trinidad and Tobago: 1) The purpose of teachers' colleges, 2) Leadership for teacher education, 3) The relationship between teachers' colleges and local schools, 4) The college programme, 5) The student and the programme, 6) The relationship between supervisors and the teachers' colleges, 7) The role of examinations, 8) The teacher selection procedure, 9) The development of a competent teaching service, and 10) The use of technologies in teacher training
Keywords: Teacher education